THE IMPLEMENTATION OF USSR (UNINTERRUPTED SUSTAINED SILENT READING) ON STUDENTS’ READING MOTIVATION AT ANANDA ISLAMIC SCHOOL - Muhammad Abduh Almanar (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
ABSTRACTThe present study will investigate the effect of implementing USSR (Uninterrupted Sustained Silent Reading) program at national plus school Ananda Islamic School. Iinterview and field observation was designed for data collection. To succeed the program, the students freely choose the storybook they like and they would be given special time at school to read during the program. The teacher will show a role model and a value of reading by joining the program of reading books with a pleasant, relaxed atmosphere and lack of pressure. This study will use an observation log, questionnaire surveys, and semi-structured interviews. 20 students were observed during USSR program within 4 weeks including a survey and 5 students will be taken as a sample through purposive sampling method.Keywords: EFL Learning, Uninterrupted Sustained Silent Reading (USSR), Reading achievement, Reading Comprehension